One-pot radiosynthesis of O-[18F]fluoromethyl-D-tyrosine via intra-molecular nucleophilic 18F-fluorination with 1, 2, 3-triazolium triflate salt precursor. (February 2018) - Kim, Ho Young; Park, Chansoo; Lee, Ji Youn; Chi, Dae Yoon; Lee, Yun-Sang; Jeong, Jae Min
Abstract: A radiolabeled amino acid O -[ 18 F]fluoromethyl-D -tyrosine (D-[ 18 F]FMT) has been reported to show high tumor uptake. However, introduction of [ 18 F]fluoromethyl group was difficult and was an issue to be solved. We solved it by using a precursor containing 1, 2, 3-triazolium salt. D-[ 18 F]FMT was synthesized from (R)−1-((4-(2-(( tert -butoxycarbonyl)amino)−3-((3, 4-dimethylbenzyl)oxy)−3-oxopropyl)phenoxy)methyl)−3-methyl-4-phenyl-1 H −1, 2, 3-triazol-3-ium trifluoromethanesulfonate via intra-molecular 18 F-fluorination and subsequent removal of the protecting groups. The total synthesis time was 65 min (including purification) and the overall radiochemical yield was 9% based on the isolated product (not decay-corrected). The resulting D-[ 18 F]FMT was obtained with high radiochemical purity (> 99%) and specific activity (100–150 GBq/μmol). D-[ 18 F]FMT also achieved excellent results in pharmacological evaluation such as stability test and protein binding assay. We expect that this simple one-pot labeling method would help using D-[ 18 F]FMT more widely. Graphical abstract: